Preparos do solo para eucalipto em segunda rotação: propriedades físicas e químicas e crescimento inicial - França, Jéssica Silveira (2017)
Reforestation areas of forest plantation, which are cultivated in a second rotation, may have the soil structure altered by compaction from the surface to the deeper layers, because of the traffic of machines during harvesting operations of the previous planting, i.e. first rotation. Efficient soil preparation techniques are required to reduce compaction and provide an appropriate physical environment to the growth and development of eucalyptus, with the least environmental degradation and the lowest cost of operations. The aim of this study was to evaluate the effect of soil tillage systems on soil physical properties and the initial growth of Eucalyptus saligna in second rotation in an Ultisol. The study was carried out in a second rotation area of eucalyptus, in Arroio dos Ratos-RS. The experimental design was of randomized blocks, with three replications. Soil tillage systems were: conventional subsoiling, interrupted every 4 to 4 m, in the direction of slope (SC); subsoiling, crosswise the slope direction, with stump cutter (SN); subsoiling with Savannah subsoiler, plus ridge, with stump cutter (SS); and mechanical digging with Rotree (CR). After the soil tillage, E. saligna seedlings were planted. In each tillage system, in the layers 0.00-0.10, 0.10-0.20, 0.20-0.30, 0.30-0.60, 0.60-1.00 m soil samples with preserved structured were collected to evaluate the soil bulk density (Ds), total porosity (Pt), macroporosity (Mac), microporosity (Mic), soil water retention, available water content (AD) and penetration resistance (RP). Samples with altered structure were used for soil chemical analysis and water retention curve in the soil with psychrometer. In the layer of 0.20-0.30 m, the Ds was close to the BDc LLWR for the tillages and in the SN this value exceeded this limit. The subsoiling and the digging provided high values of Mac up to the layer of 0.20-0.30 m. In the layer of 0.30-0.60 m there was a significant difference, where SS, SC and SN preparations provided higher Mac and lower CR. Among the tillages systems Mic was significantly higher in CR, SC and SN and lower in SS, in the layer of 0.30-0.60 m. Soil AD revealed low water availability to plants in all treatments. The RP of bench up to 0.30 m was less than 2 MPa in all the tillages, while the field resistance had values of 2 MPa up to 0.20 m. At greater depth, restricting RP values for the development of plants were observed. The SS tillage in the reforestation area provided greater benefits to the plants in the initial stage of development. From the evaluation of the soil physical properties it was not possible to detect the effect of soil tillage on the initial establishment of E. saligna plants. Evaluation of the growth of E. saligna plants was a good indicator of the effect of soil tillage systems on initial growth.